Demographic, Injury Characteristics, and Comorbidity Differences Between Youth with >28 Day and >90 Day Recovery from Concussion. Issue 5 (31st May 2022) - Young, Julie A.; Maki, Aaron; Feiss, Robyn; Yang, Jinzhen; Cuff, Steven C.
Background: The identification and comparison of risk factors between concussed children with symptom resolution >28 days and those with symptom resolution >90 days may aid in clinical care. Purpose: The objective of this study was to identify demographic, comorbidity, and injury factors associated with prolonged (>28 days) and extended (>90 days) concussion recovery among children aged 10 to 18 years with concussions. Methods: Demographics, injury characteristics and comorbidities were recorded in patients aged 10-18. We assessed the associations of patients' demographics, comorbidities, and injury characteristics with the outcome variable of concussion symptom resolution >28 days post-injury using two-level, Generalized Linear Mixed model (GLMM). We repeated the analysis for concussion symptom resolution >90 days post-injury. Odds ratios(OR) and 95% confidence intervals(CI) were reported. Results: A total of 4, 937 concussions were analyzed. Of these, 32.6% had resolution >28 days and an additional 20.1% had resolution >90 days after injury. Risk factors for symptom resolution >28 days included female sex, (OR=1.22, 95% CI=1.03, 1.44), ADD/ADHD diagnosis (OR=1.31, 95% CI=1.00, 1.72), those with one (OR=1.41, 95% CI=1.17, 1.71), two (OR=1.41, 95% CI=1.02, 1.95), or three or more previous concussions (OR=2.08, 95% CI=1.42, 3.05), higher initial symptom score (OR=1.04, 95% CI=1.04, 1.05), and greater days from injury to first visit (OR=2.80, 95% CI=2.53, 3.09). Risk factors for >90 days to recovery included older age group (OR=1.66, 95% CI=1.18, 2.32) in 15-18 year olds compared to 10-14 year olds, two (OR=1.84, 95% CI=1.10, 3.07), or three or more (OR=2.30, 95% CI=1.27, 4.19) previous concussions, history of headaches (OR=0.65, 95% CI=0.46, 0.93), anxiety disorder diagnosis (OR=1.66, 95% CI=1.04, 2.64), higher symptom scores at first visit, (OR=1.01, 95% CI=1.00-1.01), and a greater number of days from injury to first visit (OR=1.29, 95% CI=1.20-1.39). Discussion: Female sex and ADD/ADHD diagnosis were unique risk factors for >28 day recovery and history of headaches, anxiety diagnosis, and age were unique risk factors for >90 day recovery. For both groups, higher initial symptom scores and longer time to initial evaluation resulted in longer recovery. Future studies are needed to screen and detect children at risk for prolonged recovery during the acute phase post-injury so that appropriate clinical care can be provided to expedite concussion recovery.